LERE-KOPPELMANNÍŃ TIYKARǴÍ INTEGRALLÍQ FORMULASÍ HÁM ONNAN KELIP SHÍǴÍWSHÍ NÁTIYJE - Qutlımuratov, B.J.; Ubbiniyazova, A.B. (SCIENCE and SOCIETY, 2022)
The article uses integral formulas with holomorphic kernels. The basic Leray-Koppleman integral formula is studied. The validity of the generalization of the Cauchy-Fantappe formula is proved.